18 CLINICAL VIGNETTE: TAIL PAIN CAUSES TAIL SPIN. (1st January 2006) - Prudhomme, B. J.; Moss, C. N.; Chinnareddy, P.; Smalligan, R. D.
Abstract : Objective: To remind pediatricians of the increasing incidence of community-acquired methicillin-resistant Staphylococcus aureus (CA-MRSA) and its many dangerous complications. Case: A 4-year-old girl presented with a 5-day history of her "tail hurting, " causing difficulty sitting in her car seat and 3 days of high fevers. No history of recent trauma, infections, or sick contacts. PMH: No hospitalizations, surgeries, medications, or pertinent family or social history. PE: Ill-appearing girl, T 103, P 129, RR 24, O2 saturation of 96% on 4L O2, clear lungs, normal heart sounds without a rub, diffuse abdominal tenderness without hepatosplenomegaly, extremities with edema of her left gluteal area with exquisite tenderness but without any overlying erythema or skin lesions. Labs: WBC 9.4 with 40% bands, hematocrit 29.3, and ESR of 87. Electrolytes, coagulation studies, and urinalysis were normal. CXR showed small left pleural effusion. Bone scan and hip ultrasound were negative. MRI showed psoas and gluteal myositis without abscess. Hospital Course: The patient's blood cultures grew MRSA and she deteriorated despite treatment with IV vancomycin/gentamicin. Over the next 2 weeks her complications included pyomyositis of her left gluteal region, osteomyelitis of the left femur, septic arthritis of the left hip, pneumonia, pleural effusions, multiple abscesses, and a large pericardial effusion. She required 2 weeks on the ventilator, a pericardial window, chest tube, surgical drainage of the pyomyositis and multiple abscesses, and a laparoscopy. The patient was discharged home with linezolid after a 1 month. Discussion: While the majority MRSA sepsis cases originate in hospitalized patients, recent epidemiologic studies in various states have demonstrated an alarming increase in CA-MRSA infections with rates ranging from 12-49% in some pediatric series. The previously healthy girl presented here had no clear exposure risks and her hospital course illustrated many of the complications that can occur from this organism. This patient's presenting symptoms and physical exam were caused by pyomyositis, which is rarely seen in the USA except in immunocompromised patients. Due to the rising frequency of CA-MRSA, physicians must be prepared to diagnose and treat this infection aggressively in an attempt to prevent the significant morbidity described above as well as its associated mortality.